Perspectives of Moldavia"s Agricultural Sector After Potential Accession to the EU - Popa, Daniela; Timofti, Elena (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2012)
Development of intensive agriculture is a perspective direction in the world, but also in Moldavia. The natural factors, as well as knowledge and technology developed on this basis, ensuring a high yield, quality, competitiveness and specialization of production, will be both contributing to the development of agriculture as a branch, as well as the social efficiency of production. European integration and scientific progress offers new opportunities for raising agricultural output. The goal of the paper was to characterize perspectives of Moldavia’s agricultural sector following country’s potential accession to the European Union. As a conclusion we can say that the main factors in ensuring the competitiveness of agricultural products are quality, which manifests itself through price differentiation and diversity of sales channels.